-41=-2-13n

Simple and best practice solution for -41=-2-13n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -41=-2-13n equation:


Simplifying
-41 = -2 + -13n

Solving
-41 = -2 + -13n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '13n' to each side of the equation.
-41 + 13n = -2 + -13n + 13n

Combine like terms: -13n + 13n = 0
-41 + 13n = -2 + 0
-41 + 13n = -2

Add '41' to each side of the equation.
-41 + 41 + 13n = -2 + 41

Combine like terms: -41 + 41 = 0
0 + 13n = -2 + 41
13n = -2 + 41

Combine like terms: -2 + 41 = 39
13n = 39

Divide each side by '13'.
n = 3

Simplifying
n = 3

See similar equations:

| 0=36p^2-31 | | 4x*2+8x-32=0 | | 0=36p^2-9 | | 40=36p^2-9 | | 9x*2-21=0 | | (x-4)(x+8)=64 | | -13+y=-24 | | 13+y=-24 | | -13y=-24 | | 6x^3+4x=10x^2 | | 5x-7=3x-10 | | 5x+24(x-4)=107 | | 4x-3+2x=8x | | 6+k=14 | | (2x^2+3x-2)(3x^2-6x-5)= | | n-4=24 | | 23=-2(24-b)+3(b-3) | | 15x+21(x-2)=318 | | 4x^2+7-3=0 | | 19x-(4x-9)=84 | | 19x-3(4x-9)=84 | | 5m+10=9m-2 | | 5(6z+1)-9=146 | | 3(4x-1)=36 | | (-6)(9)= | | (4-9)= | | 4w^2=-12w-5 | | [10-2]= | | 12*-72= | | 14y=-84 | | v+-391=1255 | | v+-391=255 |

Equations solver categories